An inquiry into the nature and causes of the anticompetitive effects of horizontal shareholding, and a discussion of potential solutions under EU and UK competition law - Reyntjens, TML (2024)
Empirical research shows that when non-controlling minority shareholders of horizontal competitors overlap product market competition is reduced. This thesis first investigates the corporate law and governance mechanisms that explain how such ‘horizontal shareholders’ can cause anticompetitive effects notwithstanding their modest shareholdings. It is argued that shareholder passivity is exacerbated when shareholders invest in horizontal competitors, that activist hedge funds are less likely to succeed in their campaigns, and that executive compensation becomes less attuned to the pursuit of aggressive product market competition. Those three ‘causal mechanisms’ plausibly explain the anticompetitive effects observed in empirical research.